Modeling of Reservoir Structure by Using Magnetotelluric Method in the Area of Mt. Argopuro, East Java, Indonesia - Singarimbun, Alamta; Gaffar, Eddy Zulkarnaini; Tofani, Panji (Journal of Engineering and Technological Sciences, 2017)
The purpose of this study was to review a regional geothermal system by applying the magnetotelluric method, which is one of the geophysical methods that can be used to map subsurface resistivity structures. This method uses electromagnetic waves of natural resources, namely the interaction of the sun (solar wind) and lightning activity on earth. This study used an inverse modeling method, i.e. the non-linear conjugate gradient method, to estimate the resistivity value as a function of depth at points of sounding, while 2-dimensional modeling was used to describe the distribution of the resistivity values laterally or vertically on a trajectory of measurements. Data were collected from the area of Mt. Argopuro, East Java, where the magnetotelluric method has not been applied before. A geothermal system was found under Mt. Argopuro consisting of altered rock, reservoirs and hot rock with sources of heat associated with high resistivity values (1024 ohm.m). The area has potential for geothermal energy exploration in the future.